(3aJM QH GdHQjI aj TQM GdbUjOI GdNRQLjIs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s ((3ESeGYjd GdMSjfj GdeGdcj GdNdhJjs)
(3ChdgG (B:s
(3bGd SjOfG hehdGfG CHh jMji RcQjG GdCfUGQj GdTGaYj HSe Gddg GdQMef GdQMje GdMeO ddg GdPj hVY Yde GdYQhV dJYQa Hg ChRGf GdefXhes
(3BNQgG (B:s
(3hSCd YHO Gddg fGXegG QMeg Gddg JYGdi PG Cj gPG GdNRQLj GdCfUGQj hGdNRQLj fSHI Edi GdNRQL hgj bHjdI ef GdCfUGQ ef eWGdYgG Cj GdfGXQ ajgG EJMGag efg Cj eWGdYgG HGdOYGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 46s
(3eYLe GdeDdajf(B: 1 / 733s
(3cTa GdXfhf(B: 2 / 1337s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdYQhV hGdbhGajs